Tropical mycology. - Watling, Roy (CABI, 2002)
This second volume of Tropical Mycology contains 11 sections discussing the biology, taxonomy, phylogeny, physiology, anatomy and biochemistry of lichens and microfungi, including some plant pathogenic fungi.